Harnessing Community Potential: Financial Inclusion Strategies for SME Empowerment - Putra, Aditya Halim Perdana Kusuma (Manunggal Halim Jaya, 2024)
This research investigates community-driven financial inclusion strategies for small and medium-sized enterprises (SMEs) with a focus on understanding the dynamics, challenges, and opportunities associated with such initiatives. The qualitative research methodology is adopted, employing a systematic literature review approach. Various databases including Google Scholar, JSTOR, PubMed, and Scopus were utilized to access peer-reviewed literature spanning diverse disciplines. Inclusion criteria were predefined to ensure the relevance, scope, and quality of the selected studies. Data collection involved systematically gathering relevant information from literature sources, followed by qualitative data analysis techniques such as coding, categorizing, and thematically organizing the data. The synthesized findings underscore the importance of community-based approaches in promoting SME access to finance, building entrepreneurial capacity, and fostering inclusive growth. However, challenges such as the lack of comprehensive frameworks and consensus on effective scaling-up approaches persist. The study emphasizes the need for further research to elucidate the mechanisms through which community potential can be harnessed to empower SMEs and foster inclusive growth. Moreover, it highlights the transformative role of technology in enhancing SME financial inclusion, while also emphasizing the importance of regulatory frameworks and policy reforms in shaping the landscape of SME finance ecosystems. This research contributes to a deeper understanding of community-driven financial inclusion for SMEs and provides valuable insights for policymakers, practitioners, and researchers.